Mid-term outcomes of the Absorb BVS versus second-generation DES: A systematic review and meta-analysis. - Cordula M Felix; Victor J van den Berg; Sanne E Hoeks; Jiang Ming Fam; Mattie Lenzen; Eric Boersma; Peter C Smits; Patrick W Serruys; Yoshinobu Onuma; Robert Jan M van Geuns (PLoS ONE, 2018)
Background Bioresorbable Vascular Scaffolds (BVS) were introduced to overcome some of the limitations of drug-eluting stent (DES) for PCI. Data regarding the clinical outcomes of the BVS versus DES beyond 2 years are emerging. Objective To study mid-term outcomes. Methods We searched online databases (PubMed/Medline, Embase, CENTRAL), several websites, meeting presentations and scientific session abstracts until August 8th, 2017 for studies comparing Absorb BVS with second-generation DES. The primary outcome was target lesion failure (TLF). Secondary outcomes were all-cause mortality, myocardial infarction, target lesion revascularization (TLR) and definite/probable device thrombosis. Odds ratios (ORs) with 95% confidence intervals (CIs) were derived using a random effects model. Results Ten studies, seven randomized controlled trials and three propensity-matched observational studies, with a total of 7320 patients (BVS n = 4007; DES n = 3313) and a median follow-up duration of 30.5 months, were included. Risk of TLF was increased for BVS-treated patients (OR 1.34 [95% CI: 1.12-1.60], p = 0.001, I2 = 0%). This was also the case for all myocardial infarction (1.58 [95% CI: 1.27-1.96], p<0.001, I2 = 0%), TLR (1.48 [95% CI: 1.19-1.85], p<0.001, I2 = 0%) and definite/probable device thrombosis (of 2.82 (95% CI: 1.86-3.89], p<0.001 and I2 = 40.3%). This did not result in a difference in all-cause mortality (0.78 [95% CI: 0.58-1.04], p = 0.09, I2 = 0%). OR for very late (>1 year) device thrombosis was 6.10 [95% CI: 1.40-26.65], p = 0.02). Conclusion At mid-term follow-up, BVS was associated with an increased risk of TLF, MI, TLR and definite/probable device thrombosis, but this did not result in an increased risk of all-cause mortality.